Taking it to the Streets: Teaching Methods and Curriculum Courses On-Site with Partner Schools - Amanda Wall; Christine Draper (Middle Grades Review, 2017)
Our introductory middle grades course meets on-site in a partner school. This context for the course derives from an overall emphasis on partnerships in our College of Education. Meeting on-site affords teacher candidates more continuity in a middle level classroom so that they can observe young adolescents and middle level teaching. At the early stage of our program, this course meeting on-site helps prepare teacher candidates to contribute positively to schooling for young adolescents.
Keywords: teacher preparation; partnerships; middle level coursework